Thermo-mechanical behaviour of smart composite beam under quasi-static loading - Alebrahim, R. (Elsevier Ltd, 2018)
Experimental and numerical studies on a hybrid composite smart beam under quasi-static loading were carried out. The composite beam is consisted of two layers; carbon fibre/epoxy and SMA wire/epoxy layer. Carbon fibres as well as SMA wires were embedded in the host epoxy unidirectionally. SMA wires were programmed before being embedded in the composite beam. All thermo-mechanical properties associated with SMA wires were experimentally determined. A constant flexural load was initially applied to the middle of a simply-supported beam and temperature of the beam was then increased. The beam was heated using a thermal-chamber. During the heating process the deflection of the beam at midpoint was measured and the behaviour of the hybrid beam under incremental load was investigated. It was observed that, the presence of embedded SMA wires in the beam can effectively reduce deflection. Furthermore, using high volume fraction of fibres can cause buckling in the opposite direction of lateral force. Experimental results were compared against FE method and a perfect fit was obtained. Â© 2018 Elsevier Ltd